A constituição do fantástico em o livro dos lobos, de Rubens Figueiredo - Marques, Luís Paulo Fiúza (2019)
This research analyzes the establishment of the insólito in the tales of Rubens Figueiredo's collection, The book of the wolves (2009). For this purpose, it was searched to understand how the constituent mechanisms of the fantastic, such as the reader’s and/or the character’s hesitation, the lack of the characters’ nomenclature, the spatial inaccuracy of the narrative, the self-diegetic narrator, the behavioral and the discursive ambiguity assist in the establishment of this textual modality in the chosen corpus. Thus, this dissertation starts from the principle of the importance of the corpus reading of this study, as well as from the theoretical apparatuses such as David Roas (2001), Filipe Furtado (1980), Jaime Alazraki (2001), Remo Ceserani (2006) and Rosalba Campra (2016) etc, in order to understand the divergences and the approximations of the strands in regarding to the fantastic narrative concept. The focus of this work is on the fact that the tales start from a narrative principle that oscillates between reality and unreality. The achieved results show that there are oscillations and ruptures in the plot of these narratives, facts that establish the fantastic in the tales